- #1

- 61

- 1

my attempt.

**Let P = At least one a and at least one b**

Let Q = r=a/b

Let Q = r=a/b

Hence the proposition is simplified to,

**For all r where P Then Q**

**Negation:**

Not allr where P Then Q

Not all

=

**Atleast one**R When

**Not**(P Then Q)

**Not(P Then Q) = P And Not Q**

Hence

Atleast one R When

**Not(P Then Q)**

= Atleast one R When

**P And Not Q**

After this step i substitute back P and Q.

Is this way correct?

After this step i substitute back P and Q.

Is this way correct?